Diagnosis of Avian Pathology in the East of Algeria - Tarek , Khenenou; Mohamed, Melizi; Omar, Bennoune; Nezar, Adili (International Journal of Poultry Science, 2014)
The diagnosis requires a background of current knowledge in the field and also complementary means in which the laboratory occupies the central place for a better investigation. A correct diagnosis allows to establish the most appropriate treatment as soon as possible and avoids both the economic losses associated with mortality and growth retardation often observed in poultry further more it may reduce the high cost of treatment. Epidemiologic survey, hematologic and histopathologic study’s are three aspects of diagnosis heavily used in both human and veterinary pathology and the advanced researches in human medicine would be exploited to be applied in veterinary medicine with given modification. Whereas, the diagnostic methods in the east of Algeria are limited to the clinical signs and necropsy finding. Therefore, the diagnosis is based simply on the success or the failure of the therapeutic methods (therapeutic diagnosis).